Early-Stage Thinning for the Restoration of Young Redwood—Douglas-Fir Forests in Northern Coastal California, USA. (6th March 2012) - Plummer, Jesse F.; Keyes, Christopher R.; Varner, J. Morgan
Abstract : Among forested parks and reserves of the Pacific Coast of the United States, the restoration of late-successional conditions to second-growth stands is a management priority. Some traditional silvicultural treatments may help achieve this objective. We evaluated early-stage thinning as a restoration treatment to facilitate the growth and development of young (33- to 45-year old), homogeneous, and second-growth stands of coast redwood ( Sequoia sempervirens ) and Douglas-fir ( Pseudotsuga menziesii ). Targeting both stand-level responses and dominant (focal) tree responses for analysis, we compared structural attributes of adjacent thinned and unthinned stands, 12–17 years after thinning. Thinned stands displayed enhanced metrics of tree vigor, growth, and mechanical stability, thereby improving response to future restoration treatments and broadening the range of potential stand conditions. We conclude that early-stage thinning has been successful as a preliminary restoration treatment because it accomplished many initial goals of forest restoration, while retaining sufficient tree numbers to buffer against possible attrition from future disturbances.